Homeostase de cultivares de soja em diferentes ambientes e densidades de semeadura - Soares, Igor Oliveri (2015)
Soybeans are the main product of the Brazilian agriculture. However, this culture is highly influenced by factors from the environment, such as population density and predictable and unpredictable environmental factors. With the increase of soybean cultivation in the state of Minas Gerais, the study of adaptability and stability of soybean cultivars in different environments and plant densities are necessary. To this end, we conducted two separate studies. The first aimed to study the effect of different plant density in agronomic soybean characters, and identify cultivars with wide adaptability to different growing environments and seeding rates. Were evaluated six soybean cultivars under four different densities (100, 200, 300 and 400 000 plants.ha-1) in 9 different environments in the state of Minas Gerais. The BRSMG 760SRR and BRSMG 820RR cultivars have better average performance for all environment and studied seeding rates. The population of 300,000 plants.ha-1 shows as the most suitable for soybean cultivation in the evaluated environments. The second work was to study the adaptability and stability, as well as the identification of cultivars that contribute less to the G x E interaction in Minas Gerais. Were evaluated six soybean cultivars in 36 different environments of the state, in a randomized block design with three replications. For the analysis of adaptability and stability, were used methods of Wricke (1965) and Anicchiarico (1992). The interaction was decomposed according to the methodology proposed by Cruz; Castoldi (1991). The BRSMG 820RR and BRSMG 760SRR cultivars show wide adaptability and stability. The cultivar BRSMG 820RR has better confidence index and small contribution to the interaction.